Influence of +3.00 D and +4.00 D near addition on functional outcomes of a refractive multifocal intraocular lens model - Rabsilber, Tanja Marina; Rudalevicius, Paulius; Jasinskas, Vytautas; Holzer, Mike P.; Auffarth, Gerd U. (Journal of cataract and refractive surgery, 2013)
Purpose - To clinically evaluate different near additions (adds) (+3.00 diopters [D] and +4.00 D) of the M-flex 630F refractive multifocal intraocular lens (IOL). - Setting - Departments of Ophthalmology, University of Heidelberg, Germany, and Lithuanian University of Health Sciences, Kaunas, Lithuania. - Design - Clinical prospective nonrandomized unmasked study. - Methods - Preoperatively, cataract patients were assigned to receive bilateral +3.00 D IOLs, +4.00 D IOLs, or +3.00 D (dominant eye) and +4.00 D (nondominant eye) IOLs. Follow-up examinations were performed up to 6 months postoperatively and included refraction, visual acuity (near at 40 cm and distance), the defocus curve, contrast sensitivity, and a subjective questionnaire. - Results - Fifty-two patients were enrolled. No significant differences were found in the visual acuity results (P>.05). Four to 6 months postoperatively, the following median uncorrected and corrected distance visual acuity, uncorrected and distance-corrected near visual acuity, and corrected near visual acuity (logMAR) were found in all patients: −0.08, −0.12, 0.20, 0.10, and 0.10. Ninety-eight percent of patients reported being satisfied. The highest near peak versus the biggest intermediate decline in the median monocular defocus curves comparing +3.00 D and +4.00 D multifocal IOLs (logMAR) were 0.16 at 40 cm versus 0.22 at 33 cm (P=.24) and 0.38 at 66 cm versus 0.54 at 50 cm (P<.01). - Conclusion - Compared with the +4.00 D add, the +3.00 D near add gave better intermediate results in the defocus curve without compromising distance or near visual acuity. - Financial Disclosure - Drs. Rabsilber, Holzer, and Auffarth have received travel reimbursement and lecture fees from Rayner Intraocular Lenses Ltd. No other author has a financial or proprietary interest in any material or method mentioned.
Gesehen am 10.12.2021